Efektifitas Terapi Pijat Refleksi Kaki (Foot Massage) terhadap Kualitas Tidur Pasien dengan Hipertensi - Loisa Ferawati Neldina Alle; Yoany Maria Vianney Bita Aty; Pius Selasa; Trifonia Srinurwela; Aben B.Y Romana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Background: Hypertensive patients also often experience sleep disorders. To overcome sleep disorders in hypertensive patients, pharmacological and non-pharmacological therapies can be carried out. One of the non-pharmacological therapies that can be applied is foot reflexology therapy, which is useful for reducing pain, preventing complications, improving the immune system, controlling stress, overcoming headaches, and reducing dependence on antihypertensive drugs. Objective: This study aims to determine the effect of foot massage therapy on the sleep quality of hypertension patients in the working area of the Oesapa Health Center, Kupang City in 2024. Methods: This study used quantitative design with a pre-experimental approach, precisely one group pre-post design. The population in this study is all hypertension patients registered at the Oesapa Health Center in Kupang City, with a sample of 50 people. Results: The results of the study using the Wilcoxon Signed-Rank Test showed a significant effect of foot reflexology therapy on the sleep quality of hypertensive patients, with a value of p = 0.000 (p < 0.05). Conclusion: Foot massage therapy has a positive effect on improving sleep quality in hypertensive patients in the work area of the Oesapa Health Center.